Bilateral acute pyelonephritis with left renal artery aneurysm as a cause of bilateral spontaneous subcapsular haematoma: lessons learnt - Barad, Bhaumik (BMJ Case Rep, 2021)
Forniceal ruptures after acute pyelonephritis are relatively common. Bilateral spontaneous subcapsular haematoma (SSCH) is an uncommon sequela to pyelonephritis. We report a case of SSCH where the underlying cause of haematoma was a vascular anomaly. A 38-year-old woman with diabetes presented with fever, flank pain and shock following cystoscopy and Double J stenting done elsewhere. CT abdomen showed left subcapsular renal haematoma, managed by pigtail insertion. Postoperative CT showed right renal subcapsular haematoma and left moderate renal subcapsular haematoma. Renal angiogram showed pseudo-aneurysm on the left middle polar artery for which selective embolisation was performed. Physicians and urologists who come across SSCH for which no definite aetiology could be identified should keep in mind the possibility of an underlying vascular anomaly that could precipitate such a condition. The purpose of this report is to highlight the importance of remembering vascular causes in such unexplained cases of SSCH.